Identification of Nipaecoccus (Hemiptera: Coccomorpha: Pseudococcidae) species in the United States, with descriptions of Nipaecoccus bromelicola sp. n. and the male of N. floridensis Beardsley - Von Ellenrieder, Natalia; Watson, Gillian W.; Kinnee, Scott A. (Zootaxa, 2018)
The adult female and male of Nipaecoccus bromelicola sp. n. are described, based on specimens on bromeliads in Californian nurseries and intercepted from Mexico and Guatemala, countries believed to be within the native range of this species. The male of N. floridensis Beardsley is also described, illustrated, and diagnosed from known congeners. An identification key to adult females of Nipaecoccus species recorded from the United States (including its overseas territories) is presented. Molecular characterizations based on COI are provided for N. bromelicola, N. floridensis, N. nipae and N. viridis.